Th17/Treg balance: the bloom and wane in the pathophysiology of sepsis - Liu, Xinyong; Chen, Longwang; Peng, Wei; Deng, Hongsheng; Ni, Hongying; Tong, Hongjie; Hu, Hangbo; Wang, Shengchao; Qian, Jin; Liang, Andong; Chen, Kun (Frontiers in Immunology, 2024)
Sepsis is a multi-organ dysfunction characterized by an unregulated host response to infection. It is associated with high morbidity, rapid disease progression, and high mortality. Current therapies mainly focus on symptomatic treatment, such as blood volume supplementation and antibiotic use, but their effectiveness is limited. Th17/Treg balance, based on its inflammatory property, plays a crucial role in determining the direction of the inflammatory response and the regression of organ damage in sepsis patients. This review provides a summary of the changes in T-helper (Th) 17 cell and regulatory T (Treg) cell differentiation and function during sepsis, the heterogeneity of Th17/Treg balance in the inflammatory response, and the relationship between Th17/Treg balance and organ damage. Th17/Treg balance exerts significant control over the bloom and wanes in host inflammatory response throughout sepsis.